Assessing Global Kidney Nutrition Care. Issue 1 (January 2022) - Wang, Angela Yee-Moon; Okpechi, Ikechi G.; Ye, Feng; Kovesdy, Csaba P.; Brunori, Giuliano; Burrowes, Jerrilynn D.; Campbell, Katrina; Damster, Sandrine; Fouque, Denis; Friedman, Allon N.; Garibotto, Giacomo; Guebre-Egziabher, Fitsum; et al.
Visual Abstract: Abstract : Background and objectives: Nutrition intervention is an essential component of kidney disease management. This study aimed to understand current global availability and capacity of kidney nutrition care services, interdisciplinary communication, and availability of oral nutrition supplements. Design, setting, participants, & measurements: The International Society of Renal Nutrition and Metabolism (ISRNM), working in partnership with the International Society of Nephrology (ISN) Global Kidney Health Atlas Committee, developed this Global Kidney Nutrition Care Atlas. An electronic survey was administered among key kidney care stakeholders through 182 ISN-affiliated countries between July and September 2018. Results: Overall, 160 of 182 countries (88%) responded, of which 155 countries (97%) answered the survey items related to kidney nutrition care. Only 48% of the 155 countries have dietitians/renal dietitians to provide this specialized service. Dietary counseling, provided by a person trained in nutrition, was generally not available in 65% of low-/lower middle–income countries and "never" available in 23% of low-income countries. Forty-one percent of the countries did not provide formal assessment of nutrition status for kidney nutrition care. The availability of oral nutrition supplements varied globally and, mostly, were not freely available in low-/lower middle–income countries for both inpatient and outpatient settings. Dietitians and nephrologists only communicated "sometimes" on kidney nutrition care in ≥60% of countries globally. Conclusions: This survey reveals significant gaps in global kidney nutrition care service capacity, availability, cost coverage, and deficiencies in interdisciplinary communication on kidney nutrition care delivery, especially in lower-income countries.